PAUPERISM IN THE RISE OF SOCIAL POLICY OF GREAT BRITAIN - E. Sklyarova (Гуманитарные и юридические исследования)
He paper examines the problems of pauperism as the factor of the rise of social policy of Great Britain in the first half of the XIX century. The problem of misery, as a part of social policy of every state of the world, had its historical peculiarities of solution in Great Britain that depended on the growth and migration of population, traditions of the state and local government. The role and dynamics of pauperism in the rise of social policy of Great Britain is a topical problem in domestic and foreign historiography. In the first half of the XIX century, the problems of pauperism were consistently analyzed by the parliament and the press, philosophies and lawyers, statistics and doctors. During the period of urbanization after the introduction of the system of population census, the pauperism began to seen as a coercive burden of taxation. The author concludes that after the Union with Ireland in 1800, during the epoch of urbanization, the rise of social policy took place on the base of statistics analysis, changes of the poor laws, the introduction of the healthcare system in the towns of the United Kingdom of Great Britain and Ireland. According to the new Poor law of 1834 in England and Wales, the capable population must provide themselves outside the parish. The new law became the starting point of utilitarian distribution of taxes and state expenses, the rise of the social policy, coordinated not by the parishes, but by the new state authorities in line with the new poor law. Then social reforms spread in Scotland and Ireland. It was supposed to create the state system of social assistance for the poor, woman, children, the sick, widows and orphans all over the kingdom. The activity of the Commission for the Poor laws was controlled by the parliament through reports; it was discussed in the press. The pauperism reform was aimed at cardinal decision of the problem of taxation, public health, modernization of the system of social allowance, and the provision of the welfare to the whole society. During the urbanization period, the United Kingdom of Great Britain and Ireland fell from the parochial system of the poor relief to the modernization of the social expenses and healthcare in the towns.